BVD-2 outbreak leads to high losses in cattle farms in Western Germany. Issue 1 (September 2015) - Gethmann, Jörn; Homeier, Timo; Holsteg, Mark; Schirrmeier, Horst; Saßerath, Michael; Hoffmann, Bernd; Beer, Martin; Conraths, Franz J.
Abstract: In November 2012, a dairy farmer in the district Kleve first observed a reduction in milk yield, respiratory symptoms, nasal discharge, fever, sporadic diarrhoea and sudden deaths in dairy cows and calves. In the following months, further farms were found infected with cattle showing similar clinical signs. An epidemiological investigation was carried out to identify the source of infection, the date of introduction, potential transmission pathways and to analyse the extent of the epidemic. Furthermore, laboratory analyses were conducted to characterise the causative agent. BVDV had been diagnosed in the index herd in December 2012, but due to the atypical clinical picture, the virus was not immediately recognised as the causative agent. Further laboratory analysis showed that this outbreak and subsequent infections in the area were caused by a BVD type 2c virus with a characteristic genome insertion, which seems to be associated with the occurrence of severe clinical symptoms in infected cattle. Epidemiological investigations showed that the probable date of introduction was in mid-October 2012. The high risk period was estimated as three months. A total of 21 affected farms with 5325 cattle were identified in two German Federal States. The virus was mainly transmitted by person contacts, but also by cattle trade and vehicles. The case-fatality rate was up to 60% and mortality in outbreak farms varied between 2.3 and 29.5%. The competent veterinary authorities imposed trade restrictions on affected farms. All persons who had been in contact with affected animals were advised to increase biosecurity measures (e.g. using farm-owned or disposable protective clothing). In some farms, affected animals were vaccinated against BVD to reduce clinical signs as an "emergency measure". These measures stopped the further spread of the disease.